Steamed panax notoginseng mitigates CA-MRSA USA300-induced necroptosis in human neutrophils - Zhang, Lulu; Feng, Xiaoyu; An, Hongsa; Yang, Weifeng; Xia, Yuwen; Wen, Bo; Zheng, Haoran; Chen, Yihuan; Cheng, Yungchi; Jiang, Chunyan; Lu, Cheng; Tan, Yong (Frontiers in Pharmacology, 2025)
BackgroundCommunity-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) disrupts innate immunity by inducing necroptosis in polymorphonuclear neutrophils (PMNs), a process linked to excessive inflammation and tissue damage. CA-MRSA releases virulence factors that enhance its pathogenicity by disrupting the host’s innate immune response, particularly impairing the phagocytic function of PMNs. Steamed Panax notoginseng (S-PN), a traditional Chinese medicine (TCM), has demonstrated immune-regulatory and anti-inflammatory properties, showing promising therapeutic effects in alleviating the severe inflammatory responses induced by pathogenic microbial infections.ObjectiveThis study aims to investigate the pharmacological effects and mechanisms of S-PN alleviating CA-MRSA-induced PMN necroptosis by suppressing MRSA virulence factors and inhibiting the RIPK1/RIPK3/MLKL signaling pathway, thereby attenuating inflammatory damage.MethodsA co-culture model of MRSA USA300 strain and PMNs isolated from healthy human blood was established to observe the changes in necroptosis marker HMGB1, PMNs counts, ROS, chemokine MCP-1 and pro-inflammatory cytokines IL-1β, IL-8, TNF-α. RNA-seq was employed to analyze the effects of S-PN on the transcriptional expression of pathogenesis-related genes of MRSA. RT-PCR was utilized to validate the expression of S-PN on MRSA virulence factors and PMNs necroptosis related genes.ResultsS-PN significantly inhibited HMGB1, ROS, MCP-1, IL-1β and IL-8 in MRSA-PMN co-cultures, the PMN count in the S-PN group was higher than that in the model group. S-PN downregulated MRSA pathogenic-associated S. aureus infection and quorum sensing signaling pathways, and significantly reduced the virulence factors PSM and PVL. S-PN suppressed the expression of genes associated with necroptosis ripk1, ripk3, and mlkl in PMNs.ConclusionS-PN alleviates CA-MRSA infection-induced immune damage through dual mechanisms: suppression of bacterial virulence factors (PSM and PVL) and inhibition of PMNs necroptosis. These findings underscore its potential as a complementary therapeutic strategy against CA-MRSA infections, providing a theoretical foundation for integrating TCM into adjuvant treatments for drug-resistant bacterial infections.